JAPANESE ADVERTISEMENT FOR IMPROVING STUDENTS READING ABILITY - Indrowaty, Sri Aju (Universitas Pendidikan Indonesia (Indonesia University of Education), 2018)
Advertising is a form of communication that discloses information or messages and promotes the speaker's intent to his or her opponent. The language used in advertising is a language that is easy to understand and persuasive so that the opponent can speak as the speaker means. From advertisements in magazines, used for student learning in Dokkai 5. Dokkai or reading is a very important course for students to welcome the office work normally done by Japanese language graduates. In the office when working related Japanese often read documents and translate documents. In this research, using advertising media because it is usually written in large and striking letters.To make the reading japanese learning more interestingÂ Â Therefore, they needs to be approach that has never been done before withÂ reading japanese advertisement from japanese magazine. Reading Japanese language is usually difficult because it consists of three figures namely Hiragana, Katakana and Kanji. So that become easier for students to reading through the selected advertising media.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â This research is qualitative descriptive, and object of our study are students learning Japanese Language EducationÂ and Japanese Literature Brawijaya University Â who have passed JLPT N3 Â and already Â received materials about Dokkai 3 and Dokkai 4. Â Techniques Â data by purposive sampling and random sampling by using random numbers as much as 10% of the total population. In addition the results of this study will also describe motivation for students to improve their ability of reading. Therefore Â æŒ‡å°Ž ãƒ ã‚¤ ãƒ³ ãƒˆ (teaching points) as an effort to help the lecture to explain and possibility to use teach for higher education.Â